1995
DOI: 10.1007/bf02245628
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of acetylcholine release by flumazenil in the hippocampus of rats chronically treated with diazepam but not with imidazenil or abecarnil

Abstract: The effects of long-term treatment (three times a day for 3 weeks) with pharmacologically active doses of the novel anxiolytics and anticovulsants abecarnil (0.5 mg/kg, IP) and imidazenil (0.5 mg/kg, IP) on basal hippocampal acetylcholine release in freely moving rats were compared with those of diazepam (3 mg/kg, IP). Challenge doses of diazepam, abecarnil, and imidazenil decreased the extracellular acetyl-choline concentration in the hippocampus by the same extent in animals chronically treated with the resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 28 publications
1
5
0
Order By: Relevance
“…Of note, previous studies have reported that high dosages of diazepam (2‐10 mg/kg, i.p.) decrease acetylcholine release in rodent brains . Because the level of acetylcholine is positively correlated with spontaneous locomotor activity, we cannot rule out the possibility that impairment of diazepam‐induced reduction of acetylcholine release might contribute to the inferior response of HD mice to diazepam.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of note, previous studies have reported that high dosages of diazepam (2‐10 mg/kg, i.p.) decrease acetylcholine release in rodent brains . Because the level of acetylcholine is positively correlated with spontaneous locomotor activity, we cannot rule out the possibility that impairment of diazepam‐induced reduction of acetylcholine release might contribute to the inferior response of HD mice to diazepam.…”
Section: Discussionmentioning
confidence: 99%
“…decrease acetylcholine release in rodent brains. [35][36][37] Because the level of acetylcholine is positively correlated with spontaneous locomotor activity, 38,39 we cannot rule out the possibility that impairment of diazepam-induced reduction of acetylcholine release might contribute to the inferior response of HD mice to diazepam. Importantly, a GABA antagonist elevated the spontaneous locomotor activity and reversed the diazepam-evoked inhibitory effect on locomotor activity in WT mice, but not in HD mice, suggesting that the effect of diazepam on locomotor activity was mediated by GABA A R and that the function of GABA A R was altered in HD mice.…”
Section: Discussionmentioning
confidence: 99%
“…Our data raise the possibility that all anxiolytics may ultimately exert their clinical effects through a common mechanism, which is a reduction in anxiety-evoked increases in cholinergic neurotransmission possibly through M1 muscarinic receptors in the hippocampus. Other studies have demonstrated that systemic injections of benzodiazepines reduce hippocampal ACh efflux (Dazzi et al, 1995b). On the other hand, anxiogenic compounds like flumazenil increase hippocampal ACh levels (Imperato et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Most interestingly, this acetylcholine release was not seen in the partial agonists imidazenil and abecarnil, which has no efficacy at the α 1 subtype. 79 The fact that benzodiazepine withdrawal is marked by an acetylcholine increase in the nucleus accumbens, which is also seen in other drug withdrawals, further begs clarification of the benzodiazepine–acetylcholine affiliation, and possibly of subunit-specific involvement, which has been overlooked. 78 , 79 …”
Section: Mechanism Of Benzodiazepine Addictionmentioning
confidence: 99%